Understanding conversational joking : a cognitive-pragmatic study based on Russian interactions - Thielemann, Nadine (Pragmatics & beyond, 2020)
"This book examines the diverse forms of conversational humor with the help of examples drawn from casual interactions among Russian speakers. It argues that neither an exclusively discourse-analytic perspective on the phenomenon nor an exclusively cognitive one can adequately account for conversational joking. Instead, the work advocates reconciling these two perspectives in order to describe such humor as a form of cognitive and communicative creativity, by means of which interlocutors convey additional meanings and imply further interpretive frames. Accordingly, in order to analyze cognition in interaction, it introduces a discourse-semantic framework which complements mental spaces and blending theory with ideas from discourse analysis. On the one hand, this enables both the emergent and interactive character and the surface features of conversational joking to be addressed. On the other, it incorporates into the analysis those normally backgrounded cognitive processes responsible for the additional meanings emerging from, and communicated by jocular utterances"--